A Quest on the Development of Feminism in America in Riding Freedom and Fingersmith - Anna Sriastuti (TEKNOSASTIK, 2023)
The feminist movement in America is experiencing rapid development. The early feminist idea about woman's right to vote has developed on other issues, including sexuality and reproductive rights, ideas about universal femininity, the body, gender, and heteronormativity. In its development, feminism is sometimes associated with lesbianism. This linkage occurs because lesbian and feminist criticism grow in response to patriarchal oppression. Raised as an orphan, the two main female characters in Riding Freedom struggle to survive and achieve their freedom and happiness. Charlotte in Riding Freedom obscures her feminist identity to get equal opportunities with men. Susan in Fingersmith fights for her rights, even though she engages in lesbianism. By using these two novels as primary data, and data on the development of feminism in America as secondary data, this study aims to show the evolution of feminism in America, starting from the issue of voting described in The Riding Freedom, to the issue of lesbianism in Fingersmith's novel as the effect of disappointment from man's oppression. Feminist criticism and lesbian criticism are the two theories used in this research. This study finds that American women's struggle to gain equality with men requires a long process. The trauma of men's oppression supports the practice of lesbianism in America.